Pest and Diseases Control Using Synthetic and Botanical Pesticides on Several Wheat Varieties - Nurnina Nonci; Amran Muis (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
The research was carried out to find out the effect of wheat varieties and types of pesticide to control the naturally occurred pests and diseases. The research was designed in a split plot experiment with three replications. The main plot was 3 botanical pesticides (eugenol+eugenol acetate+caryophillene, azadirachtin, citronellal) and 1 synthetic pesticide (dimehypo 550 g/l) and 1 control (distilled water). The subplot was 4 wheat varieties (Guri 1, Guri 3, Guri 4, and Guri 6). Twice application of botanical pesticides was carried out at 30 and 60 days after planting (DAP). Results showed that in both vegetative and generative stage, two main pests were found, namely: Atherigona sp. and stem borer Sesamia inferens. Shoot fly incidence occured before the application of pesticide treatments. The percentage of incidence ranged from 10.33% at Guri 1 to 35.00% at Guri 6. No interaction among the applied treatments was observed on the average percentage of stem borer incidence on both growth stages. The visibly found disease was leaf blotch disease caused by Bipolaris sorokiniana. All evaluated varieties were very susceptible to leaf blotch. The harvestable grain yield was very low due to the attacks of shoot fly, stem borer and also high incidence of leaf blotch.